THE ELECTRONIC CLASSROOM (Author: Jay Phipps) - Cartwright, Glenn F. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1982)
Jay Phipps. THE ELECTRONIC CLASSROOM. Toronto-Ontario: Canadian Education Association, 1932. 39 pp. $4.00.